2011
DOI: 10.20870/oeno-one.2011.45.1.1484
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced yield and fruit quality of redglobe grapevines by abscisic acid (ABA) and ethanol applications

Abstract: <p style="text-align: justify;"><strong>Aims</strong>: Redglobe has become a popular table grape cultivar in Egypt. However, in warm climates the berries often fail to develop a full red color in addition to having lower total soluble solids (TSS) at harvest time. Here we evaluate the potential for enhancing the quality of Redglobe grapes with applications of abscisic acid (ABA) and ethanol under field conditions.</p><p style="text-align: justify;"><strong>Methods and result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 25 publications
4
6
0
Order By: Relevance
“…Yield and cluster weight is mainly depending on berry weight. The results of berry weight were in similar to noticed by Peppi et al (2007a), Omran (2011) and Deng et al (2019) for 'Redglobe', Peppi et al (2007b), Peppi and Fidelibus (2008), Lurie et al (2009) and Ferrara et at. (2013) for 'Crimson Seedless' grapes, and Kishino and Roberto (2007) for 'Rubi' grape, when they applied PGRs.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Yield and cluster weight is mainly depending on berry weight. The results of berry weight were in similar to noticed by Peppi et al (2007a), Omran (2011) and Deng et al (2019) for 'Redglobe', Peppi et al (2007b), Peppi and Fidelibus (2008), Lurie et al (2009) and Ferrara et at. (2013) for 'Crimson Seedless' grapes, and Kishino and Roberto (2007) for 'Rubi' grape, when they applied PGRs.…”
Section: Discussionsupporting
confidence: 86%
“…The conversion of these L*, a*, and b* to lightness, chroma, and hue showes into lower lightness and hue values and in general. Reductions of L*, C* and h˚ in grape skin, due to application of ABA, ethephone or both together, were previously observed by Kim et al (1998), Peppi et al (2006); Lurie et al (2009), Omran (2011), Ferrara et al (2013), and Olivares et al (2017 . But, Cantín et al (2007) found that h˚ and L* values were not differed than the control when ABA or ethephone were applied.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The soluble solids content in harvest musts were similar in grapes treated with ABA and untreated (Table 2), consistent with other authors' findings (Amiri and Parseh, 2011;Delgado et al, 2004). Nevertheless, as with ethephon, ABA tended to decrease the TA and raise the pH of the must in all seasons studied, which is consistent with previous results obtained in table grape cultivars (Omran, 2011;Peppi et al, 2007;Reynolds et al, 2016;Yamamoto et al, 2015). However, most studies in the literature have not observed changes in must TA associated with the application of ABA (Cantin et al, 2007;Delgado et al, 2004).…”
Section: Must Compositionsupporting
confidence: 91%